The Use of Bahasa Indonesia in the ELT Classroom - Baharuddin Pasaribu (TEFLIN, 2001)
This paper presents a survey of use of Bahasa Indonesia in ELT classroom. The respondents of this survey were 265students from various private universities in Bogor . It was assumped that all respondents who answered the questionnsires understood the aims of the survey. The results show, among others, that many of the students stated that Bahasa Indonesia should be used in ELT classroom and almost half the number of the students liked their teachers use of Bahasa Indonesia. Some required conditions to use Bahasa Indonesia include the difficultly of the concepts to be explained, the degree of comprehension of the students, and class administration.